Effects of long-term inhaled steroid use on bone mineral density in asthma patients - Tug, T; Kamanli, A; Tug, E (Hogrefe & Huber Publishers, 2001)
Asthma is a chronic inflammatory disease of the airways. Inhaled corticosteroids are the most effective and most frequently used antiinflammatory drugs in the treatment of asthma. It is well known that long-term systemic steroid therapy causes osteoporosis, whereas it is thought that inhaled forms do not cause this side effect, Despite the recent disagreeing reports, it has been suggested that the use of inhaled steroids are associated, with findings of biochemical bone changes, Therefore, we measured the bone mineral densities (BMD) of 18 patients (15 female, 3 male) with bronchial asthma receiving long-term inhaled steroids by X-ray absorptiometry technique and compared the results with those of 14 health) control subjects (12 female, 2 male) who had been matched according to age, sex, menopausal state, and body mass index (BMI). Results: There were no detectable significant difference between the BMD levels of left hip (trochanter major, neck of femur, Ward's triangle) and lumbar area of the spine (L2-L4) (p > 0.05).
Keywords: bone mineral density; long-term inhaled steroids; side effect